Approximation of fixed points for enriched Bγ,µ mapping using a new iterative algorithm in CAT(0) space - N. Goswami; D.D. Pathak (Қарағанды университетінің хабаршысы. Математика сериясы, 2025)
In this paper, we define enriched Bγ,µ mapping in CAT(0) space and derive some fixed point results for such mapping with the help of averaged mapping. Our results extend some existing results. A new iterative algorithm is developed in CAT(0) space to approximate the fixed point of enriched Bγ,µ mapping. ∆-convergence and strong convergence of this iterative algorithm for enriched Bγ,µ mapping is proved.